PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS SMART BOX DALAM MATA PELAJARAN IPA UNTUK MENINGKATKAN POTENSI BELAJAR SISWA MADRASAH IBTIDAIYAH - Nur Aini, Linda; Niken Septantiningtiyas; Muhammad Mushfi El Iq Bali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science learning in elementary schools often faces challenges in attracting students' interest and explaining complex materials effectively, so that innovations in learning media are needed that can increase student engagement. This study aims to analyze the application of interactive learning media based on Smart Box in science subjects to improve students' learning potential. The method used is a quantitative approach with a case study design, involving interviews, observations, and data analysis from teachers and students at MI Azzainiyah II Grinting, Probolinggo. The results of the study indicate that the use of Smart Box can increase student engagement in class discussions, facilitate understanding of complex science materials, and create a more interactive and interesting learning experience. However, several technical challenges such as device problems and student difficulties in using technology were also found, which require further attention. The implications of these findings indicate that interactive technology can be an effective tool in improving the quality of learning, as long as it is supported by adequate infrastructure. From these activities, it can be concluded that children will be more interested in exploring learning materials with fun techniques, in addition to eliminating children's boredom when learning, learning media also provides many benefits for children and makes classes more effective and enjoyable, with the presence of media.